Blood flow analyses by intraoperative transit‐time flow measurements of free flaps for head and neck reconstructions: A prospective single‐center study. Issue 2 (4th October 2022) - Ritschl, Lucas M.; Niu, Minli; Wolff, Constantin T.; Schwarz, Matthias; Roth, Maximilian; Wolff, Klaus‐Dietrich; Fichter, Andreas M.
Abstract: Background: The behavior of blood flow changes within free flaps following microvascular anastomosis is not well described in the literature. The aim of this study was to determine the immediate blood flow behavior of different free flaps as reference values for various clinical applications. Methods: Intraoperative transit‐time flow measurements were performed on patients receiving free flap transfer in the head and neck area comprising radial forearm flaps (RFF), peroneal artery perforator flaps (PAP), anterolateral thigh flaps (ALT), vastus lateralis flaps (VLF), parascapular flaps (PSF), latissimus dorsi flaps (LDF), fibula free flaps (FFF), deep circumflex iliac artery flaps (DCIA), and scapular flaps (SF). In accordance with a structured protocol, measurements took place at the pedicle directly before flap harvesting and at the recipient vessels 1 h after flap transfer. Heart rate, transplant weight, and other patient characteristics were recorded and analyzed. Results: A total of 129 were enrolled, comprising 66 RFF, 8 ALT, 6 PAP, 11 VLF, 3 PSF, 2 LDF, 24 FFF, 7 DCIA, and 2 SF. In most of the transplant groups, arterial perfusion increased after anastomosis at the recipient site. The arterial pulsatility index developed indirectly proportionally to arterial blood flow, whereas venous blood drainage did not show any statistically significant changes. Muscle flaps had the highest arterial perfusion before flap transfer. Composite transplants with hard and soft tissue presented the greatest increase in arterial perfusion. The lowest arterial blood flow after anastomosis was measured in PAP and RFF. In contrast, RFF and PAP presented the highest arterial perfusion per 100 g transplant weight. Conclusions: Arterial perfusion changed, whereas venous blood flow did not show any statistically significant variations in any transplant group. Perfusion of free flaps does not only depend on the recipient vessel and the recipient bed, but also on flap‐specific anatomy and physiology.